Towards a better understanding of cultural diversity approaches at school: A multi-informant and mixed-methods study. (March 2017) - Civitillo, Sauro; Schachner, Maja; Juang, Linda; van de Vijver, Fons J.R.; Handrick, Anna; Noack, Peter
Abstract: The current study investigates two types of cultural diversity approaches at school, namely (1) fostering equality and (2) promoting cultural pluralism . Adopting a mixed-methods design, this study assesses teachers' ( n = 207) and students' ( n = 1, 644) self-reported perceptions of descriptive norms and evaluates school practices and artefacts in the physical and virtual environment of 22 secondary schools in south-west Germany. Results showed that in all schools under investigation teachers and students perceived descriptive norms fostering mostly equality . A wide variety of practices and artefacts was found, revealing a third distinct cultural approach leaning towards endorsing the majority culture . Different practices and artefacts were linked to an emphasis on equality, cultural pluralism, and endorsing the majority culture . Implications for educational policy, as well as applied diversity research, are discussed.